A new estimator of mean under ranked set sampling alongside the sensitivity issue. Issue 8 (30th November 2018) - Shahzad, Usman; Hanif, Muhammad; Koyuncu, Nursel; Garcia Luengo, Amelia Victoria
Abstract: In this article, a new estimator of the population mean is proposed provided that the mean of supplementary variable is known. The proposed estimator is also discussed for the sensitivity issue. Properties such as bias and mean square error (MSE) of the proposed estimator are also derived. The new estimator is compared with their counter parts under ranked set sampling (RSS). It turns out that proposed estimator provide encouraging results in terms of (MSE) for both situations. A simulation study is carried out for illustration.